Managing climate change (Strategic direction (Bradford, England), 2008)
Climate change is the apex of a whole range of issues which will be crucial for our planet's future and for the generations to come - ranging from the unsustainable use of our planet's resources, peak oil, the exponential problem of waste, the population explosion. Therefore in addressing the problem of climate change, businesses could address a number of strategic but inter-related issues at the same time. This e-book provides a selection of new articles and reviews of recently published articles on managing climate change aimed at businesses and business managers.